21ST INTERNATIONAL CONFERENCEON STATISTICAL SCIENCES - Abdur Rasheed (Baqai Journal of Health Sciences)
The Office of Research, Innovation, and Commercialization (ORIC) at Dow University of Health Sciences (DUHS), in collaboration with Baqai Medical University (BMU), successfully hosted the 21st International Conference on Statistical Sciences. The three-day conference, held from December 9 to 11, 2024, brought together renowned experts, researchers, and students worldwide to discuss the theme "Mobilizing Data Science & Big Data to Achieve SDGs."